Magnesium sulfate in preeclampsia: Broad indications, not only in neurological symptoms - De Oliveira, Leandro [UNESP]; Korkes, Henri; Rizzo, Marina de; Siaulys, Monica Maria; Cordioli, Eduardo (Elsevier, 2024)
The role of magnesium sulfate for treatment of eclampsia is well established. The medication proved to be superior to other anticonvulsants to reduce the incidence of recurrent convulsions among women with eclampsia. Additionally, magnesium sulfate has been indicated for women with preeclampsia with different severe features. However, despite these recommendations, many clinicians are still not confident with the use of magnesium sulfate, even in settings with high incidence of preeclampsia and unacceptable rates of maternal mortality. This review brings basic science and clinical information to endorse recommendations to encourage clinicians to use magnesium sulfate for patients with all severe features of preeclampsia, not only for women with neurological symptoms. Additionally, other benefits of magnesium sulfate in anesthesia and fetal neuroprotection are also presented. Finally, a comprehensive algorithm presents recommendations to manage patients with preeclampsia with severe features between 34 and 36+6 weeks.
Keywords: Eclampsia; HELLP syndrome; Magnesium sulfate; Maternal mortality; Preeclampsia; Prematurity; Severe hypertension